Molecular Characteristics and Pathogenicity of a Novel Transplacental Rat Cytomegalovirus - Loh, Hwei San (2005)
Cytomegalovirus (CMV) is a species-specific betaherpesvirus which causes acute, persistent and latent infections in both humans and animals. CMV is the most frequent congenital infection in humans. RCMV strain ALL-03 was the first CMV ever isolated from the placenta and uterus of the house rat (Rattus rattus diardii). As such, hypothetically, this RCMV should be a distinct strain from the existing isolates that is capable to cross placenta and infect the fetus. The objectives of the study were (i) to identify the novelty of the RCMV strain ALL-03, (ii) to characterize its immediateearly (IE) genes, and (iii) to determine its pathogenicity by developing the in utero transmission and neonatal infection models in rats. Overall, the present study signifies the virological and molecular detection of the RCMV antigen, DNA and mRNA in addition to the serological demonstration of the RCMV-specific immune response. Other than the traditional diagnostic methods, the study had also used advanced techniques, for examples, double antibody sandwich enzyme-linked immunosorbent iv assay (DAS-ELISA), quantitative real-time reverse transcription-polymerase chain reaction (RT-PCR) and real-time PCR. The study was commenced by characterizing the strain ALL-03. Upon infection, the virus showed delayed cytopathology, cellassociation, low maximum titres, the presence of herpesviral inclusion bodies and herpesvirus related particles in infected rat embryonic fibroblast (REF) cells; specific antigen-antibody reaction with RCMV strain Maastricht; and rat-specific are all in accord with a RCMV. The genetic difference at the genome level with that of Maastricht, English, UPM/Sg and UPM/Kn strains had confirmed its novelty. The first recognized genes expressed during CMV infection, the IE genes were studied by analyzing the mRNA transcripts of infected-REF cells. The cDNA libraries were cloned into plasmids for sequencing. Each sequence was then probed towards the databanks for an identity search. Following the PCR and hybridization techniques, two distinct transcripts of unknown identities within the databanks were confirmed to be of the strain ALL-03 origin. These two IE transcripts were found considerably different to the IE genes of RCMV strains Maastricht and English. Meanwhile, a real-time RT-PCR assay was developed specifically to quantify the in vitro transcription levels of the two RCMV IE mRNAs. The kinetic transcription profiles and the bioinformatics analyses suggested them as exon 4 or IE1 and exon 5 or IE2. An in utero infection model demonstrated the clinical signs, pathological changes and anatomical virus distribution to the uterus, placenta, embryo, fetus, lung, kidney, spleen, liver and salivary gland of rats. The placenta was observed to be involved in the maternofetal RCMV infection. The maternal viremia leading to uterine infection which subsequently transmitting to the fetus through the placenta is the most likely phenomenon of congenital CMV v infection in the model. The study has established a useful rat model that mimics the neonatal CMV infection in humans especially for the virus dissemination in different organs, viremia and immune response. The kinetic quantitation of the viral antigen, DNA and antibody was assessed by DAS-ELISA, real-time PCR and ELISA respectively. This neonatal rat model demonstrated a characteristic splenomegaly and acute virus dissemination in blood, spleen, liver, lung and kidney. The salivary gland infection is suggested to augment the antibody response that may be responsible for a reduction of viremia. The study has provided important new insights of CMV disease particularly for a congenital infection in humans. The exploitation of the major IE regions has permitted greatest advances as a candidate of viral-vectored immunocontraception for rat control and generation of eukaryotic expression vectors.